Productive context analisys in Colombia, measuring and application for recommendations applied on public politics of the cooperation and economic development organization - OCDE to improve productivity (2020)
The purpose of this document is to identify both the country's needs in terms of productivity and competitiveness since 2004, and its progress on achieving those in some facts. As much as the effort it will take to this goal, so not only does it hope to satisfy the country's basic needs by 2019, but by 2032 it hopes to position the national economy among the three most important in the region. It is meant, not just demanding a harldy work but also a progressive transformation due to the new public politics incorporating rules to handle tools do to such a success, this work is also meant to identify how easily will be gather to OCDE, and will allow or not achieve the goals in public politics, in which private and public fields will agree in terms of economic increases starting from actions to become a better and productive country, competitive in towards international leves.